Arnold Beckman at an Eagle Scout Award ceremony - Rothschild Photo (1957)
Arnold Beckman with George Fenniman, Charles Thomas, and unidentified individuals at an Eagle Scout dinner. Based on the décor, the photographs of Beckman and the Boy Scout were taken in Beckman's office.
Keywords: Boy Scouts; Beckman, Arnold O.; Boy Scouts of America; Scientific apparatus and instruments; Globes; Award presentations; Beckman Instruments, Inc.; Eagle Scouts; Hydrogen-ion concentration--Measurement--Instruments